Analisis Pelaksanaan Kurikulum 2013 pada Mata Pelajaran Matematika di SMP Negeri 2 Wonogiri Tahun Ajaran 2016/2017 - Ratnasari, Indah, Prof. Dr. Budi Murtiyasa, M.Kom (2016)
The research is conducted to describe how the implementation process of learning mathematics by using curriculum 2013 and to find out any difficulties experienced by teachers in the implementation. This research is a qualitative descriptive. The subjects were 2 Math teacher SMP Negeri 2 Wonogiri. Data collection techniques using the method of observation, interviews and documentation. Data validation was done by triangulation method by comparing the data of observation, interviews, and documentation. Data analysis techniques performed by stage data reduction, data presentation, verification and conclusion. The result showed that (1) The study of mathematics curriculum in 2013 consisted of planning, implementation, assessment processes and learning outcomes have been quite good, (2) constraints experienced math teachers in curriculum implementation in 2013 among other things difficult to change the mindset of teachers and students, the ability students who are not evenly distributed, time, and complex judgments. This is due to a lack of mental readiness of teachers and learners in the face of the new curriculum (Curriculum 2013).